Cultivating Communicative Agency in Islamic Religious Education Teacher: The Impact of Social-Media-Mediated Video Pedagogy on Religious Digital Literacy and Speaking Skills - Abdul Rahman; Yudi Gucandra; Zulfani Sesmiarni; Junaidi; Putri Laila Ramadhani; Hidayatul Dina; Rabiatul Adawiyah; Faizul (Nadwa: Jurnal Pendidikan Islam, 2026)
As social media becomes increasingly integrated into higher education, limited empirical research has examined its role in developing religious digital literacy and communication skills among prospective Islamic teachers. This study examines the impact of the 30HariBersuara project, a social media–based video learning innovation, on the religious digital literacy and public speaking competencies of Islamic Religious Education (IRE) students. The study employed a quantitative one-group posttest design with a retrospective pretest involving 97 matched student responses. Data were collected using a five-point Likert-scale questionnaire measuring five dimensions: self-confidence and public speaking, literacy and insight, creativity and content production, readiness for the teaching profession, and self-development. The findings revealed an increase in the overall mean score from 3.31 (moderate) to 4.16 (high), representing a gain score of 0.85. The greatest improvement was observed in the literacy and insight dimension (0.99), followed by self-confidence and public speaking (0.89). These findings suggest that social media–based video learning can effectively strengthen students' religious digital literacy and communication competencies while preparing them for their future roles as Islamic educators in the digital era.